Selectively aligned cellulose nanofibers towards high-performance soft actuators. (May 2019) - Kuang, Yudi; Chen, Chaoji; Cheng, Jian; Pastel, Glenn; Li, Tian; Song, Jianwei; Jiang, Feng; Li, Yiju; Zhang, Ying; Jang, Soo-Hwan; Chen, Gang; Li, Teng; et al.
Abstract: Motion of plants in response to environment stimuli (e.g., opening and closing of pinecones) often finds its origin in the organized microscopic structures of the moving part, which sheds light on a new way to design and fabricate high-performance biomimetic soft actuators. In this paper, we design a micro-patterned soft actuator consisting of a selectively aligned cellulose nanofiber layer and a passivation layer. The unique structure of the cellulose nanofiber layer is achieved by an evaporation-assisted self-assembly method (inspired by the "coffee ring" effect). Benefiting from the hydrophilic, nanoporous and well-aligned cellulose nanofiber network, the resultant soft actuator demonstrates a fast (response time less than 1s), extremely powerful ( ∼ 1000 times lifting weight ratio), and controllable response to external environmental stimuli, which is comparable to the best performing soft actuators reported in the literature. Mechanics modeling further reveals that the well-aligned cellulose nanofiber layer plays an important role in both the final curvature and generation of the actuation forces. Proof-of-concept demonstrations of the micro-patterned soft actuators as mechanical arms and soft walking robots indicate their great potential for soft robots and biomimetic systems.